St. Kitts and Nevis. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Presents the results of IICA in St. Kitts and Nevis in 2008 in relation to the state of agriculture and rural life, the implementation of the national technical cooperation agenda, interagency cooperation, horizontal technical cooperation, new opportunities for technical cooperation, and the organized activities